International Food Policy Research Institute (IFPRI) Information Products Open Access Policy (IPOA) - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
In pursuit of its mandate to provide research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition in developing countries, staff at the International Food Policy Research Institute (IFPRI) generate a wide range of research-based Information Products including a) publications, b) datasets, c) databases, d) software, application and source codes, e) audio, video, and images, f) tools and models, and g) websites and web services. IFPRI views the products of its research as International Public Goods and is committed to enabling their widespread distribution and use by providing unrestricted public access.